Distinct roles of UVRAG and EGFR signaling in skeletal muscle homeostasis - Min Jeong Kim; Daniella Febbraro; Sofia Farkona; Taylor Gillmore; Joe Eun Son; Romario Regeenes; Huntley H. Chang; Evan Pollock-Tahiri; Jiaqi Yang; Yoo Jin Park; Tharini Sivasubramaniyam; Soo Jung Oh; et al. (Elsevier, 2021)
Objective: Autophagy is a physiological self-eating process that can promote cell survival or activate cell death in eukaryotic cells. In skeletal muscle, it is important for maintaining muscle mass and function that is critical to sustain mobility and regulate metabolism. The UV radiation resistance-associated gene (UVRAG) regulates the early stages of autophagy and autophagosome maturation and plays a key role in endosomal trafficking. This study investigated the essential in vivo role of UVRAG in skeletal muscle biology. Methods: To determine the role of UVRAG in skeletal muscle in vivo, we generated muscle-specific UVRAG knockout mice using the Cre-loxP system driven by Myf6 promoter that is exclusively expressed in skeletal muscle. Myf6-Cre+ UVRAGfl/fl (M-UVRAG−/−) mice were compared to littermate Myf6-Cre+ UVRAG+/+ (M-UVRAG+/+) controls under basal conditions on a normal chow diet. Body composition, muscle function, and mitochondria morphology were assessed in muscles of the WT and KO mice at 24 weeks of age. Results: M-UVRAG−/− mice developed accelerated sarcopenia and impaired muscle function compared to M-UVRAG+/+ littermates at 24 weeks of age. Interestingly, these mice displayed improved glucose tolerance and increased energy expenditure likely related to upregulated Fgf21, a marker of muscle dysfunction. Skeletal muscle of the M-UVRAG−/− mice showed altered mitochondrial morphology with increased mitochondrial fission and EGFR accumulation reflecting defects in endosomal trafficking. To determine whether increased EGFR signaling had a causal role in muscle dysfunction, the mice were treated with an EGFR inhibitor, gefitinib, which partially restored markers of muscle and mitochondrial deregulation. Conversely, constitutively active EGFR transgenic expression in UVRAG-deficient muscle led to further detrimental effects with non-overlapping distinct defects in muscle function, with EGFR activation affecting the muscle fiber type whereas UVRAG deficiency impaired mitochondrial homeostasis. Conclusions: Our results show that both UVRAG and EGFR signaling are critical for maintaining muscle mass and function with distinct mechanisms in the differentiation pathway.